Neuronal T-Cell Autoreactivity Is Amplified in Overweight Children With New-Onset Insulin-Requiring Diabetes - Buryk, Melissa A. (Diabetes Care, 2015)
OBJECTIVE: Disease-associated T-cell autoreactivities are seen in most type 1 diabetic patients and are thought to emerge before islet autoantibodies, but host factors that impact autoimmune elements remain uncertain. We assessed if adiposity and measures of insulin sensitivity impact T- and B-cell autoimmunity in children with insulin-requiring diabetes. RESEARCH DESIGN AND METHODS: Insulin-requiring children and adolescents diagnosed between January 2004 and June 2008 were studied (n = 261): age 9.7 ± 4 years, 92% white, and 60% male. T-cell responses to 10 diabetes-associated antigens, β-cell autoantibodies (GADA, IA-2A, IAA, and ICA), BMI z score (BMIz), and waist percentile were measured at onset and 3 months later. RESULTS: All but one subject had either T- or B-cell autoimmunity. Diabetes-associated T-cell autoreactivities were found in 92% of subjects. Higher amplitude T-cell autoreactivities to neuronal diabetes-associated autoantigens were seen in those with the highest BMIz quintile, BMI ≥85th percentile (P < 0.05), and waist circumference ≥85th percentile (P < 0.05). There were no relationships between the number of T-cell reactivities or T-cell diversity with adiposity measures or autoantibody number or type. Patients with positive T-cell reactivities but without autoantibodies had the highest BMIz (P = 0.006). CONCLUSIONS: Our observations link obesity and diabetes-related autoimmunity, suggesting an amplification of neuronal T-cell autoimmunity associated with adiposity and/or insulin resistance, with obesity-related inflammation possibly enhancing islet autoimmunity.